Interference Avoidance and Mitigation Techniques for Hybrid Satellite-Terrestrial Mobile Backhaul System - Xiaoyan ZHANG; He WANG (天地一体化信息网络)
One of the best ways is to assume that satellite and terrestrial segments share the same spectrum in order to utilize more eff ciently the scarce and expensive spectrum resource.The interference avoidance and mitigation technologies such as antenna arrays, multi-antenna communication technologies, intelligent backhaul nodes, interference-aware power allocation method, and licensed shared access (LSA) were deployed in a hybrid satellite-terrestrial mobile backhaul (MBH) system to demonstrated how to enhance the overall capacity of the hybrid system and reuse the spectrum at diff erent systems on a noninterfering basis.Through theoretical analysis and numerical simulations, it is observed that these interference avoidance and mitigation techniques mentioned above could be used eff ciently to meet the enormous capacity demands of future backhaul networks, off -load the terrestrial segment, manage intrasystem (terrestrial) and the intersystem (satellite-terrestrial) co-channel interference (CCI), lead to hardware costs and energy-consumption savings, and improve spectrum utilization eff ciency.